Manajemen Kinerja Guru di Pondok Pesantren Nidaul Quran - Maya Ulandari (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2023)
This study aims to analyze teacher performance management at Pondok Pesantren Nidaul Quran in Tanjung Village, Sarolangun Regency. The research focuses on planning, implementation, evaluation, and both supporting and inhibiting factors in managing teacher performance. A qualitative approach was employed, with data collected through observation, in-depth interviews, and document analysis. The findings reveal that teacher performance management in this pesantren has attempted to balance religious and academic aspects. However, limited facilities, lack of professional training, and budget constraints remain significant challenges. Improvement efforts include regular coaching, strengthening the leadership role of pesantren authorities, and fostering collaboration between teachers and students. This research contributes to the development of educational management in pesantren, particularly in enhancing the quality of learning through teacher performance.